La distribución de las oclusivas orales en la toponimia prerromana de la Bética (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Even though the toponyms in the Baetica come from different languages, they all have a common phonological feature which leads us to think that, before the latinization took place, they had all acquired the features of a previous common language.